Os agricultores ecologistas nos mercados para alimentos orgânicos:: contramovimentos e novos circuitos de comércio - Niederle, Paulo Andre (Sustainability in Debate, 2014)
The paper analyzes the counter-movements created by ecologist farmers in reaction to processes of institutionalization of agro-ecology and conventionalization of organic foods. This reaction involves strategies of re-localization and reterritorialization of circuits of commerce. The results come from recent research of Rede Ecovida de Agroecologia in the metropolitan region of Curitiba. The research focus on the intricate socio-cultural architecture that sustains the new circuits of commerce, which are used to legitimize moral values that distinguish an ecological food from a organic product.